2014
DOI: 10.3854/crm.5.084.erosa.v1.2014
|View full text |Cite
|
Sign up to set email alerts
|

Kinixys erosa (Schweigger 1812) – Forest Hinge-back Tortoise, Serrated Hinge-back Tortoise, Serrated Hinged Tortoise.

Abstract: summary. -The Forest Hinge-back Tortoise, Kinixys erosa (Family Testudinidae), is a forest tortoise with considerable range over the continuous Guinea-Congo rainforest region in West and Central Africa. It is a medium-sized to large tortoise, with a carapace length reaching ca. 400 mm, and males larger than females. Tortoises of the genus Kinixys can close themselves entirely within their shells through a unique posterior carapacial hinge. Kinixys erosa inhabits the lowland evergreen forest, marshy areas, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…One explanation may be that the ecological niche of chimpanzees only rarely overlaps with that of hinge-back tortoises. Hinge-back tortoises show a relatively rich ecological diversity and are found in lowland evergreen forest, marshy areas, and gallery forests growing along rivers and streams 4244 . For instance, Vonesh 44 reported that hinge-back tortoises are widely distributed throughout Uganda, but seem to be absent from intact forest areas with relatively high densities of chimpanzees such as the Kibale National Park.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One explanation may be that the ecological niche of chimpanzees only rarely overlaps with that of hinge-back tortoises. Hinge-back tortoises show a relatively rich ecological diversity and are found in lowland evergreen forest, marshy areas, and gallery forests growing along rivers and streams 4244 . For instance, Vonesh 44 reported that hinge-back tortoises are widely distributed throughout Uganda, but seem to be absent from intact forest areas with relatively high densities of chimpanzees such as the Kibale National Park.…”
Section: Discussionmentioning
confidence: 99%
“…Forest hinge-back tortoises (Family Testudinidae) are medium- to large-sized reptiles with a carapace of approximately 400 mm length (weighing about 600–1500 g) 42,43 . Males are larger than females.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of C. senegalensis (one of three Trionychids in our analyses and a species listed as VU by the IUCN; Diagne et al, 2016) near the top of our conservation priority analysis may be viewed as a potential shortcoming of our methodology when compared with the lower placement of species with EN statuses, such as K. erosa and C. sulcata (Luiselli and Diagne, 2014;. However, while C. senegalensis is known to be one of the more common species in many of the places it has been sampled (Senegal: McGovern, unpublished data; South Sudan: Demaya et al, 2019;Benin: Luiselli et al, 2020;Ghana: Gbewaa et al, 2021;Nigeria: Luiselli, Akani and Eniang, unpublished data) this is not the first analysis in which it has received a high threat ranking (Luiselli, 2009).…”
Section: Discussionmentioning
confidence: 95%